Dispersión retributiva, estructura salarial y resultados de la organización: On modelo de invstigacion - G. Sánchez Marín (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2008)
Although there are quite a lot of studies that have tried to identify factors shaping pay structures, not many works have showed their effects on organizations. Analysis of compensation differences between jobs and levels -pay dispersion- report more controversies and contradictions than consensus. This study attempts to sort out some of these questions trough a research model based on main theoretical perspectives -tournament and equity- and empirical findings. This model gives support to interrelations between pay dispersion and performance, remarking the role and influence of moderating factors. Based on the model, we propose several research propositions, suggesting possibilities for future studies.
Keywords: 330; pay dispersion; pay structure; performance; theoretical model; research propositions